Performance Audit: Importance and Prospects within the Public Financial Control System - O. I. Lozitskaya; N. L. Voronina (Финансы: теория и практика)
The article discusses the concept and application of performance audit in public administration integral to the modern public financial control system. The aim of the study is to analyze the public financial control system using modern approaches to audit performance and its development prospects in Russia. The authors use general scientific and special research methods (analysis, synthesis, induction, deduction), as well as methods of economic theory: positive analysis and scientific abstraction. The study analyzed basic approaches to defining the concept of “performance audit”, its idea, the most important issues that it solves, and development prospects. The study proposed the concept of a two-level control system: the internal control bodies represented by the Federal Treasury of the Russian Federation should supplement the bodies conducting the performance audit. In the future, this will help build a full performance audit system of the use of public financial resources. As a result, the authors identified the problems of implementing the proposed concept. The key problem is the different statuses of the Federal Treasury of Russia and the Accounts Chamber of the Russian Federation, with different regulation of their activities. The authors named directions for the development of the public financial control system when it is impossible to implement the proposed system. In particular, they proposed to review and precisely regulate the activities of all public financial control bodies. The authors concluded that there is still no regulatory, legal and informational base necessary to switch to the proposed two-level performance audit system. Further studies may provide a deeper look at the possibilities and prospects of the integrated implementation of the performance audit system in the general government sector.